Efektifitas Penegakan Hukum Tindak Pidana Perdagangan Orang Melalui Prostitusi Online Di Wilayah Hukum Kepolisian Daerah Jambi - Suzanalisa Suzanalisa; Ibrahim Ibrahim; Nuraini Zachman (Universitas Batanghari Jambi, 2021)
Online prostitution continues to develop in Indonesia which has a negative impact on the Indonesian state, including damaging the nation's morals, especially the nation's successor generation as the nation's successor relay so that it can threaten the survival of the nation and state in the future, the fading of the values of Pancasila as the nation's ideology which is used as a foundation of the founding of the State of Indonesia. Religious, moral, and social values will be marginalized, and only liberal culture will be left behind, prostitution can be used by outsiders to damage national resilience, bring down the identity of the Indonesian people who are famous for their noble character and uphold the values of eastern culture and religion and prostitution. Online prostitution can cause and spread venereal and skin diseases as online prostitution in the Jambi Regional Police jurisdiction has increased. Therefore, it is necessary to conduct a study using the Juridical Empirical research method which aims to analyze the effectiveness of law enforcement in law enforcement of the crime of trafficking in persons through online prostitution in Indonesia. The Jambi Regional Police Legal Area, analyzes the factors that influence the effectiveness of this crime and provides solutions for Law Enforcement of the Crime of Trafficking in Persons Through Online Prostitution in the Daer Police Legal Area ah Jambi so it runs effectively